Design and analysis of umbrella trials: Where do we stand? - Ouma, Luke O.; Wason, James M. S.; Zheng, Haiyan; Wilson, Nina; Grayling, Michael (Frontiers in Medicine, 2022)
Background: The efficiencies that master protocols can bring to modern drug development in the era of precision medicine have seen their increased utilisation in precision oncology. Growing interest has also resulted in their consideration in non-oncology settings. Umbrella trials are one class of master protocol design that evaluates multiple targeted therapies in a single disease setting. Despite the existence of several reviews of master protocols, the statistical considerations of umbrella trials have received more limited attention. Methods: We conduct a systematic review of the literature on umbrella trials, examining both the statistical methods that are available for their design and analysis, and their use in practice. We pay particular attention to considerations for umbrella designs applied outside of oncology. The systematic search was performed in PubMed on 12th May 2021. Findings: We identified 38 umbrella trials. To date, most umbrella trials have been conducted in early phase settings (73.7%, 28/38) and in oncology (92.1%, 35/38), had a binary endpoint (71.1%, 27/38) and were randomised (50.0%, 19/38). Several trials had adaptive features (39.5%, 15/38) and the frequentist framework was mostly used for the design and analysis (39.5%, 15/38). The quality of statistical information available about conducted umbrella trials to date is poor; for example, it was impossible to ascertain how sample size was determined in most trials (55.3%, 21/38), the statistical framework (to be) used in the analysis (52.6%, 20/38) and whether any error rates were controlled (63.2%, 24/38). The literature on statistical methods for umbrella trials is currently sparse. Conclusions: Umbrella trials have potentially great utility to expedite drug development, including outside of oncology. However, to enable lessons to be effectively learned from early use of such designs, there is a need for higher-quality reporting of umbrella trials. Furthermore, if the potential of umbrella trials in precision medicine is to be realised, further methodological research is required.